Inelastic Behavior of Eccentrically Braced Frames with Vertical Links: A Numerical Study - Shendri, Christina Natasha; Tjahjanto, Helmy Hermawan; Nugroho, Wivia Octarena; Pratiwi, Naomi (Rekayasa Sipil, 2025)
Eccentrically Braced Frames (EBFs) are seismic-resistant steel structures with horizontal or vertical energy-dissipating links designed to enhance ductility. To promote sustainability, future designs are moving toward easily replaceable structural systems that enable rapid post-earthquake rehabilitation. However, EBFs with horizontal links present challenges in repairing damaged links due to interference with other components, particularly beams. As an alternative, vertical links offer the potential to serve as "replaceable elements." Despite this advantage, no specific design guidelines currently address the lateral support requirements for EBFs with vertical links, unlike the horizontal ones. This study analyzes the inelastic behavior of EBFs with vertical links using numerical methods based on the finite element method. The results indicate that vertical link length classification and capacity design methods specified for horizontal links also apply to vertical links. This is evidenced by the shear force values in the three samples representing short, medium, and long links, resulting in values of 2.15Vp, 1.32Vp, and 1.13Vp, respectively, with the shortest link classified as a shear link. The degradations of the horizontal load capacities due to the application of initial deformation, simulating the first buckling mode, are less than 0.01% for all configurations. This verifies that without lateral supports, the vertical links could still effectively dissipate energy through flexural and/or shear yielding without lateral instability issues.